2018
DOI: 10.1101/380295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The macrocyclizing protease butelase 1 remains auto-catalytic and reveals the structural basis for ligase activity

Abstract: Plant asparaginyl endopeptidases (AEPs) are expressed as inactive zymogens that perform seed storage protein maturation upon cleavage dependent auto-activation in the low pH environment of storage vacuoles. AEPs have attracted attention for their macrocyclization reactions and have been classified as cleavage or ligation specialists. However, we have recently shown that the ability of AEPs to produce either cyclic or acyclic products can be altered by mutations to the active site region, and that several AEPs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In a comprehensive analysis of Ftshi mutant phenotypes, Mishra et al (2019) have found that inactive FtsH homologs affect chloroplast function and plant development. Furthermore, in the right conditions, some proteases can ligate peptides, for example in the production of cyclic peptides by asparaginyl endopeptidases such as legumain and butelase (Zauner et al , 2018; James et al , 2019). Also, the presence of smaller molecular weight protein products is not necessarily the result of proteolysis.…”
Section: Protease Substratesmentioning
confidence: 99%
“…In a comprehensive analysis of Ftshi mutant phenotypes, Mishra et al (2019) have found that inactive FtsH homologs affect chloroplast function and plant development. Furthermore, in the right conditions, some proteases can ligate peptides, for example in the production of cyclic peptides by asparaginyl endopeptidases such as legumain and butelase (Zauner et al , 2018; James et al , 2019). Also, the presence of smaller molecular weight protein products is not necessarily the result of proteolysis.…”
Section: Protease Substratesmentioning
confidence: 99%
“…However, cyclic peptides that are smaller than nine residues cannot be cyclized . To facilitate the broad utilisation of butelase1, it has been developed to be produced recombinantly in E. coli (James et al, 2019) and yeast (Pi et al, 2019).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Enzyme mediated protein/peptide ligation has been exploited for a number of applications in peptide ligation (Proft 2010, Chen et al 2015, peptide cyclization (Saska et al 2007, Nguyen et al 2015b, Nguyen et al 2016a, 2016b, Amy et al 2019, Hemu et al 2016, peptide labelling (Popp et al 2007, John et sl. 2009, Yamamoto and Nagamune 2009, John et al 2008, Antos et al 2016, Craik 2010, Conlan et al 2011, Giang et al 2014, Saska et al 2007), protein-lipid conjugation (John et al 2008, protein thioesters synthesis (Cao et al 2015), living-cell surface labelling (Bi et al 2017, Swee et al 2015 and antibodydrug conjugation (Fang et al 2016).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%